ANALISIS EFISIENSI MATERIAL BAJA DALAM STRUKTUR KUDA-KUDA ATAP PADA BANGUNAN KOMERSIAL - Manurung, Edison Hatoguan; Hutagaol, Kerlima; Putrafakhmi, Dizzy (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This paper examines the efficiency of steel material use in commercial building roof trusses. The analysis was conducted by comparing several types of steel profiles using manual calculations and structural software, based on Indonesian National Standards (SNI) standards. The goal was to identify the most material-efficient configuration without compromising strength and stability. The results indicate that selecting the right profile can save up to 25% on material, resulting in a more economical and efficient design.